Impact of mitral intervention on outcomes of patients with mitral valve dysfunction and annulus calcification. Issue 6 (23rd January 2022) - Kato, Nahoko; Pellikka, Patricia A.; Scott, Christopher G.; Lee, Alexander T.; Jain, Vaibhav; Eleid, Mackram F.; Alkhouli, Mohamad A.; Reeder, Guy S.; Michelena, Hector I.; Pislaru, Sorin V.; Bagameri, Gabor; Crestanello, Juan A.; et al.
Abstract: Objectives: To compare all‐cause mortality in patients with mitral annulus calcification (MAC) and severe mitral valve dysfunction (MVD) who received standard mitral intervention versus no intervention. Background: Patients with MAC often have high surgical risk due to advanced age, comorbidities, and technical challenges related to calcium. The impact of a mitral intervention on outcomes of patients with MAC and severe MVD is not well known. Methods: Retrospective review of patients with MAC by transthoracic echocardiography (TTE) in 2015 at a single institution. Patients with severe mitral stenosis (MS) or regurgitation (MR) were analyzed and stratified into two groups: surgical or transcatheter intervention performed <1 year after the index TTE, and no or later intervention. The primary endpoint was all‐cause mortality. Results: Of 5502 patients with MAC, 357 had severe MVD (MS = 27%, MR = 73%). Of those, 108 underwent mitral intervention (surgery = 87; transcatheter = 21). They were younger (73 ± 11 vs. 76 ± 11 years, p < 0.01) and less frequently had cardiovascular diseases compared with no‐intervention. Frequency in women was similar (45% vs. 50%, p = 0.44). During median follow‐up of 3.2 years, the intervention group had higher estimated survival than those without intervention (80% vs. 72% at 1 year and 55% vs. 35% at 4 year, p < 0.01). Adjusted for age, eGFR, LVEF < 50%, and pulmonary hypertension, mitral intervention was an independent predictor of lower mortality (hazard ratio = 0.66, 95% confidence interval 0.43–0.99, p = 0.046). Conclusion: Patients with MAC and severe MVD who underwent mitral intervention <1 year from index TTE had lower mortality than those without intervention. Mitral intervention was independently associated with lower mortality.